ركن الخطأ في المسؤولية المدنية - نويري عفاف - بن صالح وسام (المسيلة, 2022)
في هذه الدراسة موضوع ركن الخطأ في كل من المسؤولية العقدية والمسؤولية التقصيرية ، وعالجنا في هذا البحث المكانة التي يحتلها الخطأ من خلال توضيح الاحكام القانونية المعالجة له في التشريع الجزائري، وخلصنا إلى أن المسؤولية المدنية تعرف نوعا من العجز نتيجة التطور التكنولوجي الذي صاحبه تعدد الاصابات والأضرار وصعوبة اثبات الخطأ التقصيري، مما بدأ الحديث عن نظام قانوني قائم بدون خطأ وهو ما يسمى بالمسؤولية الموضوعية. الكلمات المفتاحية:ركن الخطأ، المسؤولية العقدية، المسؤولية التقصيرية، التشريع الجزائري Abstract: In this study, we have dealt with the issue of the element of error in both contractual and default liability. In this research we have studied the state that error occupied by clarifying the legal provisions addressed to it in the Algerian legislation, and we have concluded that civil liability knows a kind of disability as a result of the technological development that accompanied by multiple injuries, damage and difficulty in proving error, which led to began speaking of a legal system that is in place without error and is called objective civil liability. Key words : Corner of error, contractual liability, tort liability, Algerian legislation
Keywords: ركن الخطأ، المسؤولية العقدية، المسؤولية التقصيرية، التشريع الجزائري